Creation of intersectoral panel for the proper treatment of children and adolescents in the municipality of Cabra - López-Verdugo, Isabel; Ridao, Pilar; Hidalgo García, María Victoria; López Chica, María Belén; Moreno González, Rosario; Roldán Juez, Rocío; Sánchez Hidalgo, José (Cuadernos de Trabajo Social, 2023)
This paper presents an interdisciplinary project to advise local agents in the municipality of Cabra based on a rights-based approach to child and adolescent care. The advice focused on the creation of an intersectoral panel to promote proper treatment, helping to consolidate a networking model. A participatory action research (PAR) methodology was applied. Information was gathered on the main needs of the local population, available resources and the degree of coordination of those resources. A total of 70 participants from different professional and community backgrounds were involved. Children, adolescents and their families were also involved. Asset mapping has facilitated the organization of a wide range of available resources. This mapping includes the different public and private intervention sectors in the municipality. The results showed a need to promote and improve the coordination of resources. It is proposed to create and implement an intersectoral panel as a useful tool to promote networking in the municipality of Cabra.